The role of agricultural commercialization for smallholders productivity and food security : an empirical study in rural Ethiopia - Tirkaso, Wondmagegn Tafesse (SLU/Dept. of Economics, 2013)
For the past few decades, continuing economic and demographic change across the world has brought an excess demand for different types of agricultural products. As a result, policy makers and international institutions have been advocating several policy instruments aimed to boost agricultural production and food security. In most cases, however, the potential role of smallholder commercialization has not been given due attention despite its importance. Therefore, this research assesses the potential role of commercialization for smallholder agricultural productivity and food security in Ethiopian farm households. Econometric model based on stochastic frontier analysis is used as the main technique in addressing the predetermined research questions. As a data set, the 2009 Ethiopian rural household survey compiled by International Food Policy Research Institute is used. Findings show that farmers are only 40.2 percent efficient relative to the most efficient farmers in the sample using the current input level. The variables related to educational level, access for radio, access for cell phone and level of commercialization are positively linked with technical efficiency. Results imply that output can be increased up to 59.8 percent by improving the existing input mixes used in the production process. Furthermore, estimated results for the determinants of farmers’ commercialization identified different types of market as the main statistically significant variables. Besides, the amount of households' budget share allocated for food consumption expenditure is indirectly associated with level of commercialization suggesting possibility of substantial influence on quality and quantity of households' food consumption. Finally, with respect to policy recommendations, the overall results suggested that policy makers and international donors should prioritize their effort on increasing smallholders' degree of market participation as one of the main instrument in improving agricultural productivity and food security.